Marta Płaska - role model in the business development of modern nursing. - Gierczak, Grażyna (Nursing Problems / Problemy Pielęgniarstwa, 2016)
Introducion. Marta Płaska was an outstanding nurse who directed scrub nursing to the modernity. She was active in professional organizations. Aim of the study. Presentation of role model-scrub nurse, teacher and manager for the development of modern nursing in surgery operation. Assumptions. Marta Płaska became a model nurse-specialist, with the feature of personality, a constant work on their own development, identification with the profession, and the influence of schools and professional organizations. Her sensitivity and openness to the needs of another human being cemented School of Nursing at the Hospital of the Transfiguration in Warsaw carried out by Sister Wanda Żurawska. Marta Płaska was extremely talented scrub nurse, she worked in the First Surgery Clinic headed by Professor John Nielubowicz at the State Clinical Hospital on Lindleya street in Warsaw. She quickly promoted after two years of work in the operating entrusted with the function of the ward. She participated in the first kidney transplantation in Poland and a number of innovative surgical operations. After moving to the newly constructed clinic of hospital on Banacha street, she managed the operation block. Marta Płaska looked for modern solutions in the work of nurses and methods of sterilization. She was trained in England, Sweden, Finland, and she visited several hospitals in the United States. She represented the Polish Nurses Association at ICN Congress in Los Angeles. Her speech had inspired to organize an international scrub nurse association and had met great acclaim. Marta Płaska had exceptional organizational skills. On behalf of the International Committee of the Red Cross she took up the challenge to run operating block in the devastated hospital in Kompong Cham in very difficult and dangerous conditions. Summary. In should be emphasized the huge amount of work Marta Płaska in the development of modern nursing through innovative solutions, training of operating room and scrub nurses, exchange of experience in the international forum.